Transcription Factor UAF, Expansion and Contraction of Ribosomal DNA (rDNA) Repeats, and RNA Polymerase Switch in Transcription of Yeast rDNA - Oakes, Melanie (American Society for Microbiology, 1999)
Strains of the yeast Saccharomyces cerevisiae defective in transcription factor UAF give rise to variants able to grow by transcribing endogenous ribosomal DNA (rDNA) by RNA polymerase II (Pol II). We have demonstrated that the switch to growth using the Pol II system consists of two steps: a mutational alteration in UAF and an expansion of chromosomal rDNA repeats. The first step, a single mutation in UAF, is sufficient to allow Pol II transcription of rDNA. In contrast to UAF mutations, mutations in Pol I or other Pol I transcription factors can not independently lead to Pol II transcription of rDNA, suggesting a specific role of UAF in preventing polymerase switch. The second step, expansion of chromosomal rDNA repeats to levels severalfold higher than the wild type, is required for efficient cell growth. Mutations in genes that affect recombination within the rDNA repeats, fob1 and sir2, decrease and increase, respectively, the frequency of switching to growth using Pol II, indicating that increased rDNA copy number is a cause rather than a consequence of the switch. Finally, we show that the switch to the Pol II system is accompanied by a striking alteration in the localization and morphology of the nucleolus. The altered state that uses Pol II for rDNA transcription is semistable and heritable through mitosis and meiosis. We discuss the significance of these observations in relation to the plasticity of rDNA tandem repeats and nucleolar structures as well as evolution of the Pol I machinery.